Determinación de la prevalencia de cisticercosis en cerdos faenados en el camal municipal del cantón Pelileo - Jurado Tua, Walter Fabian (2024)
In the Pelileo canton, Tungurahua province at 2,600 meters above sea level; The prevalence of cysticercosis was determined in pigs slaughtered in the municipal slaughterhouse of the Pelileo canton; A descriptive analytical statistical model was applied in 200 pigs; Percentages, means, frequency and graph were calculated; The objectives set were: 1) identify the anatomical pathological alterations of the affected organs. 2) Carry out the economic analysis of confiscation and 3) socialize the results obtained in the investigation; The experimental variables and results were: Prevalence (PV): 2% in 200 animals, Breed (R): 4 crossbred, Sex (S): 2 Males – 2 Females, Age (E): 1 pig (3-6 months)3 pigs (7-9 months), Body Condition (C/C): 3 Skinny – 1 Lean, Presence of Cyst (PQ): 4 pigs presented in the Liver, Carcass Weight (CP): 3 pigs (61 Kg – 80 Kg) 1 pig (>81 Kg), Economic Loss from Confiscation (PED): $635.00 USD in 317.5 Kg/carcass, Origin (P): Pelileo canton; According to the statistical results obtained, the alternative hypothesis was verified; Finally, porcine cysticercosis is considered an important parasitic pathology with zoonotic risk, with great economic impact that represents the total confiscation of cysticercotic pigs, in humans it causes neurocysticercosis with great impact on public health